Terapi Slow Deep Breathing untuk Menurunkan Tekanan Darah Lansia Hipertensi: Quasi Experimental Study (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Hypertension is one of the major health problems among the elderly and poses a risk of serious complications if not properly controlled. Slow deep breathing is a relaxation technique that can be used as a non-pharmacological intervention to reduce blood pressure. This study aimed to determine the effect of slow deep breathing on blood pressure in elderly patients with hypertension at the nursing home X Jakarta. The study employed a quasi-experimental design with a pretest-posttest control group approach. A total of 26 respondents were divided into two groups: intervention and control, each consisting of 13 people. The slow deep breathing intervention was performed for 10 minutes with a breathing frequency 6-10 breaths per minute. The results showed a significant reduction in systolic and diastolic blood pressure in the intervention group after the slow deep breathing exercise. Data analysis using the Wilcoxon and Mann-Whitney tests showed a p-value <0.05, indicating a significant difference before and after the intervention. Slow deep breathing proved to be effective in reducing blood pressure and can serve as a safe, simple, and affordable non-pharmacological therapy for elderly individuals with hypertension. This intervention also has the potential to improve quality of life and reduce dependence on antihypertensive medication.